Using (I-O) tables to measure the effectiveness of public spending and trade multiples Foreign Ministry in the Iraqi economy for the period (2010-2018) - Kadom , Mohammed Hussien; Hameed , Ammar Mahmood; Kadhim, Hyder Jawad; Yossef, Anes Abdulredah (International Journal of Psychosocial Rehabilitation, 2020)
We used a new method for calculating the multiplier, which is the input and output method that contains foreign trade, and we used this method to calculate multiples at the level of each sector of the national economy in the Iraqi economy for the period (2010 - 2018). We relied on the technical transactions matrix issued by the Iraqi Ministry of Planning, the National Accounts Department for the year (2010), and we used complex sectoral growth factors to obtain the matrix in 2018, and we made a comparison between the two matrices after applying the product model used in its mathematical formula to the two matrices to solve them and obtain the sectorial outcomes and final and total demand Likewise, the added value, as we obtained sectorial interconnections in all their direct and indirect forms, forward and backward, and then sectorial multiples were obtained which we found to have decreased significantly in the year 2018 compared to 2010 and that the reason The main reason behind this decline is the weakening of the forward and backward sectorial interlink ages due to excessive dependence on the foreign trade sector, especially imports.